No other world: the poetry of Don Maclennan - Robinson, Brendon Kimbale (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2008)
This is a study of the poetry of Don Maclennan in four chapters. Chapter One explores the poetry's deep involvement with the immediate world, and with the being that encounters it. Chapter Two examines the corpus's mistrust of abstract thought, and its suggestions for alternative ways of intepreting (or at least approaching an interpretation of) our existential situation. Chapter Three deals with Maclennan's writing on the subject of death, while the final chapter looks at the response of the poetry to the fact of death: put simply, this is to learn to love the situation we are in, and to record our thoughts for future generations, thus reaching beyond death to share with others the necessarily unique experience of our one and only life.
Keywords: Maclennan, Don; Maclennan, Don -- Criticism and interpretation; South African poetry (English) -- History and criticism